The Ngejot Tradition The Ngejot Tradition Increases Religious Tolerance in Gelgel Village, Klungkung Regency, Bali.: Ngejot Tradition in Klungkung - Putu Sri Marselinawati (IAHN-TP Palangka Raya, 2022)
Abstract Heterogeneous religious life in Bali generates a high sense of tolerance in inter-religious interactions. Diversity in religious life is actually something that can beautify and enrich and enrich the atmosphere in religious life. The Ngejot tradition which is carried out on Galungan Day by the people of Gelgel Village, Klungkung Regency, Bali as a medium of adhesive religious tolerance. Ngejot as tolerance is an awareness of living in each religion, obeying the teachings of their religion and practicing noble values, maintaining and maintaining order in religious life. The existence of social interaction giving gifts in the form of food certainly improves communication between religious communities by wishing each other a happy holiday and as a moment of apology so that the holiday moment can be carried out with a clean heart. The implementation of the ngejot tradition at the Galungan celebration as a medium of social integration in fulfilling and maintaining the social structure of society. Social integration (Community integration) is the cooperation of all members of society, ranging from individuals, families, institutions, and society as a whole to produce values ??that are upheld. Social integration will be realized if it is able to control the prejudices that exist in society so that conflicts do not occur so as to realize coercive integration. Key Words: Tradition, Ngejot, Tolerance